Effects of testosterone, 17beta-estradiol, and downstream estrogens on cytokine secretion from human leukocytes in the presence and absence of cortisol - Janele, D (2006)
Estrogens at physiological concentrations are thought to play an immune-stimulating role, whereas androgens have an anti-inflammatory impact. However, their role on cytokine secretion in the presence or absence of cortisol has not been investigated. Furthermore, the role of hydroxylated estrogens downstream of 17beta-estradiol (E2) on secretion of tumor necrosis factor (TNF) is not known. In this study on peripheral blood leukocytes of healthy male subjects, we scrutinized the influence of prior sex hormones (for 24 h) with and without later addition of cortisol (for another 24 h) on stimulated secretion of TNF, IL-2, IL-4, IL-6, IL-10, and interferon-gamma (IFN-gamma). E2 stabilized or increased immune stimuli-induced secretion of TNF, IL-2, IL-4, IL-6, IL-10, and IFNgamma in relation to testosterone. Testosterone, in contrast, inhibited (IL-2, IL-4, IL-10) or tended to inhibit stimulated secretion of these cytokines (TNF, IFNgamma). This effect of E2 was pronounced at a concentration of 10(-10) M (testosterone: 10(-7) M) in the presence of cortisol. E2 (10(-8) M, 10(-10) M) and testosterone (10(-7) M) did not change glucocorticoid receptor expression. The downstream estrogens 2OH-estradiol(one), 4OH-estradiol(one), and 16OH-estradiol(one) did not stimulate TNF secretion at 10(-10) M, but even inhibited its secretion at 10(-11) M. However, the combination of 16OH-estradiol(one) on one side and 2OH-estradiol(one) or 4OH-estradiol(one) on the other side markedly stimulated TNF secretion that was only observable in the presence of cortisol. In conclusion, at physiological concentrations, E2 and a combination of downstream estrogens stabilized or increased immune stimuli-induced TNF secretion. These effects are dependent on the presence of physiological concentrations of cortisol. This study underlines the proinflammatory role of E2, which is probably dependent on conversion to a proinflammatory cocktail of downstream estrogens and the presence of cortisol.